FABRICATION OF MECHANICAL OPERATED SWEEPING MACHINE - Mr. Korshetti. V. V.; Mr. M.B.Mane; Mr. K.N.Yelameli; Mr. S.R.Wagdari; Mr. S.V.Mukade; Mr. K.R.Kalsheeti; Mr. G.S. Sangpal (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The "Fabrication of Mechanically Operated Sweeping Machine" project focuses on designing and constructing a manually powered device aimed at simplifying and improving the process of surface cleaning. Unlike electrically operated sweepers, this machine relies on mechanical motion, making it cost-effective, eco-friendly, and suitable for use in areas without access to electricity. The sweeping mechanism operates through the rotation of wheels connected to a gear-driven brush system, which collects dust and debris into a container. This design emphasizes user-friendly operation, low maintenance, and enhanced mobility, making it ideal for use in public places, institutions, and smallscale industries. The project contributes to sustainable cleaning solutions by reducing reliance on electric power while maintaining efficiency and cleanliness.